Sinosporangium fuscu m sp. nov., isolated from soil - Chanwit Suriyachadkun; Wipaporn Ngaemthao; Suwanee Chunhametha; Chitti Thawai; Jean-Jacques Sanglier (My University, 2015)
A novel actinomycete, A-T 8343T was isolated from a moist evergreen forest soil sample collected in the Trat Province, Thailand. Based on 16S rRNA gene sequence analysis, strain A-T 8343T belonged to the genus Sinosporangium and was closely related to Sinosporangium siamense A-T 1946T (98.81 %) and Sinosporangium album 6014T (98.54 %). The DNA-DNA relatedness values were 21.8-27 % with S. siamense A-T 1946T and 31.1-31.9 % with S. album 6014T, which were significantly below 70 %. The result differentiated A-T 8343T from the closest species. The organism developed spherical sporangia containing non-motile spores on aerial mycelia. The cell-wall peptidoglycan contained meso-diaminopimelic acid. The whole-cell sugars contained rhamnose, ribose, madurose and glucose. The predominant menaquinones were MK-9(H2) and MK-9(H4). The diagnostic phospholipids were phosphatidylmethylethanolamine, phosphatidylethanolamine, hydroxyl-phosphatidylethanolamine, diphosphatidylglycerol, lyso-phosphatidylethanolamine, N-acetylglucosamine-containing phospholipids, phosphatidylglycerol, phosphatidylinositol, phosphatidylinositol-mannosides, aminophosphoglycolipid and one unknown phospholipid. The major cellular fatty acids were saturated C16 : 0, iso C16 : 0, unsaturated C16 : 1 and C18 : 1. Following an evaluation of phenotypic, chemotaxonomic and genotypic characteristics, the new isolate is proposed as a representative novel species of the genus Sinosporangium to be named Sinosporangiumfuscum sp. nov. The type strain is A-T 8343T ( = BCC 52770T = NBRC 109516T).
Keywords: Phosphatidylethanolamine; Rhamnose; Strain (injury); Diamino acid; Genomics and Phylogenetic Studies